Pengaruh Financial Knowledge, Financial Attitude, Locus Of Control Terhadap Financial Management Behavior - Izza Saifullah Fatta; Jeni Susyanti; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract With the rapid development of technology and human lifestyles, they also experience developments or lifestyle improvements that ultimately have an impact on people's behavior that is too extravagant and always keeps up with the times, especially among students who always follow their ego in making decisions in considering their needs and needs. his desire to live a hedonistic life that makes students unable to manage their financial resources and manage their finances well, most students have not been able to control the expenses they make, leading to dependence on quality of life on individual capacity to manage financial affairs, the computerized economy in Indonesia is encountering extremely quick turn of events. particularly in monetary innovation (fintech). The improvement of fintech is supposed to affect financial development, both embracing ordinary and sharia frameworks, particularly during the monetary recuperation time frame during the Coronavirus pandemic. During the current pandemic, many companies are experiencing a financial decline where MSME owners must think in order to keep their finances stable, because The researcher wants to know the effect of financial management behavior in Rembang City during the Covid-19 pandemic. This type of research is using explanatory research. According to this type, this research is included in the category of quantitative research. The reason for this study was to decide the impact of Monetary Information, Monetary Mentality and Locus Of Control on Monetary Administration Conduct. The example utilized in this study is the imaginative economy entertainers in the style sub-area of Rembang City.Keywords: Financial Knowledge, Financial Attitude, Locus Of Control dan Financial Management Behavior